STRESS MANAGEMENT EDUCATION AND TRAINING PROGRAM REDUCES THE ANXIETY LEVELS OF STUDENTS FACING THE NATIONAL HIGH SCHOOL EXAM - Qomariah, Siti Nur; Iswati, Iswati; Faniwati, Faniwati; Wiyono, Elviana Putri; Amin, Nadyah Safirah; Azizah, Yesita Nur; Huda, Miftakhul (SYNTHESIS Global Health Journal, 2023)
Background. The national exam is seen by students as something scary and threatening to the future, thus increasing negative cognition and anxiety. Education will focus on individual reactions to a situation and the ability to face the exam. The purpose of this community service was to increase students' knowledge about stress management and decrease students' anxiety level in facing national school exams. Implementation Method. This community service was carried out on grade 12 students of Madrasah Aliyah Negeri Surabaya with a total of 15 people. The activity was carried out in December 2022. The method used was stress management training and a combination of several ways to reduce stress, including deep breathing relaxation techniques, positive thinking exercises, and spiritual emotional freedom technique (SEFT) exercises. Findings. The results of the activity obtained mostly students’ increased knowledge about stress management of 10 students (66.7%) and 10 students had anxiety within normal limits as many as 10 children (66.7%). Conclusion. Stress management education and training combinations are very useful for reducing student anxiety in facing school exams.